Brilliance in exile : the diaspora of Hungarian scientists from John von Neumann to Katalin Karikó - Hargittai, István; Hargittai, Balazs (Central European University Press, 2023)
"By addressing the enigma of the exceptional success of Hungarian emigrant scientists and telling their life stories, Brilliance in Exile combines scholarly analysis with fascinating portrayals of uncommon personalities. István and Balazs Hargittai discuss the conditions that led to five different waves of emigration of scientists from the early twentieth century to the present. Although these exodes were driven by a broad variety of personal motivations, the attraction of an open society with inclusiveness, tolerance, and - needless to say - better circumstances for working and living, was the chief force drawing them abroad. While emigration from East to West is a general phenomenon, this book explains why and how the emigration of Hungarian scientists is distinctive. The high number of Nobel Prizes among this group is only one indicator. Multicultural tolerance, a quickly emerging, considerably Jewish, urban middle class, and a very effective secondary school system were positive legacies of the Austro-Hungarian Monarchy. Multiple generations, shaped by these conditions, suffered from the increasingly exclusionist, intolerant, antisemitic, and economically stagnating environment, and chose to go elsewhere. "I would rather have roots than wings, but if I cannot have roots, I shall use wings," explained Leo Szilard, one of the fathers of the Atom Bomb"--